2018
DOI: 10.1177/0266666918811397
|View full text |Cite
|
Sign up to set email alerts
|

An approach to quality improvement of Nigerian university library services: A framework for effective quality management implementation

Abstract: The paper explores the different strategies in managing operations and delivering services and compares them to current trends in academic libraries in Southwestern (SW) Nigeria. The author objectively and comparatively examined the different models of quality management (QM) and strategies, from which a framework of quality improvement for Nigerian university libraries was developed. The article employed a pragmatic approach to unearth the complexities of investigating the phenomenon in academic library envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
3
7
0
Order By: Relevance
“…The current study found ISO 9000 and TQM as the predominant QM models in the Chinese context. This finding is consistent with previous studies from other countries, which similarly identified ISO 9000 [120] and TQM [5,121] as the principal QM models discussed and implemented in academic library settings. This trend reflects a widespread preference for models that have demonstrated effectiveness in enhancing service quality and operational efficiency.…”
Section: Rq 2 What Types Of Qm Models Have Been Discussed and Impleme...supporting
confidence: 92%
See 4 more Smart Citations
“…The current study found ISO 9000 and TQM as the predominant QM models in the Chinese context. This finding is consistent with previous studies from other countries, which similarly identified ISO 9000 [120] and TQM [5,121] as the principal QM models discussed and implemented in academic library settings. This trend reflects a widespread preference for models that have demonstrated effectiveness in enhancing service quality and operational efficiency.…”
Section: Rq 2 What Types Of Qm Models Have Been Discussed and Impleme...supporting
confidence: 92%
“…In addition, the intrinsic developmental needs of academic libraries were identified as the most important internal enabler in this review. This finding is in line with outcomes from the international literature, which found the comprehensive improvement of information services [40], enhancement of communication and collaboration between libraries [5,40], elevation of the libraries' quality image [38], and supportive leadership styles [5,120] as key components for internal development. These elements collectively contribute to libraries' ongoing efforts towards excellence in service quality and operational efficiency, which reflect a global consensus on the importance of developmental need in driving QM initiatives.…”
Section: Rq 2 What Types Of Qm Models Have Been Discussed and Impleme...supporting
confidence: 82%
See 3 more Smart Citations